(untitled) - Sylvia S Mader (Dubuque, Iowa, 1985)
The book is divided into 4 sections: *) Section one discusses the characteristics of life; presents the concepts of evolution, diversity and the environment. *) Section two shows that life is highly organized matter. *) Section three covers diversity of life. *) Section four discusses both traditional and modern ecology
Keywords: biology